Faktor dan Penjadualan Shift Kerja - Lientje Setyawati Maurits; Imam Djati Widodo (Faculty of Industrial Technology Universitas Islam Indonesia, 2008)
Work shift has negative effect in physical and mental health, work performance and job accident. Disturbance of circadian rhythms is indicated as source of the problems. This article explores some researches related to the impacts of work shift and establishes basic principles of work shift scheduling that considers human need and limitation. Keywords: work shift, circadian rhythms, accident, fatique.